Method for producing positive electrode active material, positive electrode active material, and battery

By exchanging Li ion for Na-containing oxide particles with P2 type structure, Li-containing oxide particles with O2 type structure were prepared, which solved the shortcomings of the existing positive electrode active substances in terms of resistance and magnification characteristics, and achieved further Excellent battery performance.

CN119306266APending Publication Date: 2025-01-14TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410912972.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-11
Filing Date
2024-07-09
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing positive electrode active substances with O2-type structure still have room for improvement in resistance and magnification characteristics in solid and liquid-based batteries.

Method used

By exchanging Li ion to Li oxide particles containing Na with P2 type structure, Li oxide particles containing O2 type structure are prepared, and their average particle size and structure are controlled to form a hollow single-layer or multi-layer structure. Spherical particles, positive electrode active substance used in solid batteries and liquid batteries.

Benefits of technology

It significantly reduces the resistance of solid batteries and improves the magnification characteristics of liquid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306266A_ABST
    Figure CN119306266A_ABST
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a positive electrode active material, a positive electrode active material, and a battery. Disclosed is a method for manufacturing a positive electrode active material having an O2-type structure and having low resistance when applied to a solid-state battery. The manufacturing method according to the present disclosure is a method for manufacturing a positive electrode active material for a solid-state battery, the method comprising: obtaining Na-containing oxide particles having a P2-type structure; and ion-exchanging at least a portion of the Na in the Na-containing oxide particles with Li to obtain Li-containing oxide particles having an O2-type structure, in which the Na-containing oxide particles are spherical particles having an average particle diameter of 1.0 [mu] m or more and less than 3.5 [mu] m, and the Li-containing oxide particles are spherical particles having a hollow single-layer structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application discloses a method for producing a positive electrode active material, the positive electrode active material and a battery. Background Art

[0002] As a positive electrode active material, a positive electrode active material having an O2 type structure is known. As disclosed in Patent Document 1, a positive electrode active material having an O2 type structure can be obtained by ion-exchanging at least a portion of Na in an oxide containing Na having a P2 type structure with Li.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-170994 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Conventional positive electrode active materials having an O2 type structure still have room for improvement in terms of resistance when applied to solid batteries, or in terms of rate characteristics when applied to liquid batteries.

[0008] Means for solving problems

[0009] The present application discloses the following multiple solutions as means for solving the above-mentioned problems.

[0010] <Option 1>

[0011] A method for manufacturing a positive electrode active material for a solid battery, comprising: obtaining Na-containing oxide particles having a P2-type structure; and exchanging at least a portion of Na in the Na-containing oxide particles for Li to obtain Li-containing oxide particles having an O2-type structure, wherein the Na-containing oxide particles are spherical particles having an average particle size of greater than 1.0 μm and less than 3.5 μm, and the Li-containing oxide particles are spherical particles having a hollow single-layer structure.

[0012] <Option 2>

[0013] The production method according to claim 1, wherein the Na-containing oxide particles contain at least one element of Mn, Ni, and Co, Na, and O as constituent elements.

[0014] <Option 3>

[0015] A positive electrode active material is a positive electrode active material for a solid battery, comprising oxide particles containing Li, wherein the oxide particles containing Li have an O2 type structure, the oxide particles containing Li are spherical particles having a hollow single-layer structure, and the oxide particles containing Li have an average particle size of greater than 1.0 μm and less than 3.5 μm.

[0016] <Option 4>

[0017] The positive electrode active material according to claim 3, wherein the Li-containing oxide particles have a diameter of less than 4.5 μm. 2 / g specific surface area.

[0018] <Option 5>

[0019] The positive electrode active material according to aspect 3 or 4, wherein the Li-containing oxide particles contain at least Li and O as constituent elements, at least one element among Mn, Ni and Co.

[0020] <Option 6>

[0021] A solid battery comprising a positive electrode active material layer, an electrolyte layer and a negative electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of Schemes 3 to 5, and the positive electrode active material layer comprises a solid electrolyte.

[0022] <Option 7>

[0023] A method for manufacturing a positive electrode active material for a liquid battery, comprising: obtaining Na-containing oxide particles having a P2-type structure; and exchanging at least a portion of the Na ions of the Na-containing oxide particles with Li to obtain Li-containing oxide particles having an O2-type structure, wherein the Na-containing oxide particles are spherical particles having an average particle size of 3.5 μm or more, and the Li-containing oxide particles are spherical particles having a hollow multilayer structure.

[0024] <Option 8>

[0025] The production method according to claim 7, wherein the Na-containing oxide particles contain at least Na and O as constituent elements, at least one element among Mn, Ni and Co.

[0026] <Option 9>

[0027] A positive electrode active material is a positive electrode active material for a liquid battery, comprising oxide particles containing Li, wherein the oxide particles containing Li have an O2 type structure, the oxide particles containing Li are spherical particles having a hollow multilayer structure, and the oxide particles containing Li have an average particle size of 3.5 μm or more.

[0028] <Option 10>

[0029] The positive electrode active material according to claim 9, wherein the Li-containing oxide particles have a diameter of 4.5 m 2 / g or more specific surface area.

[0030] <Plan 11>

[0031] The positive electrode active material according to aspect 9 or 10, wherein the Li-containing oxide particles contain at least Li and O as constituent elements, at least one element among Mn, Ni and Co.

[0032] <Plan 12>

[0033] A liquid battery comprising a positive electrode active material layer, an electrolyte layer and a negative electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of Schemes 9 to 11, and the positive electrode active material layer comprises a liquid electrolyte.

[0034] Effects of the Invention

[0035] The positive electrode active material disclosed herein has low resistance when applied to a solid battery. Alternatively, the positive electrode active material disclosed herein has excellent rate characteristics when applied to a liquid battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1A An example of a flow of a method for producing a positive electrode active material used in a solid battery is shown.

[0037] Figure 1B An example of a flow of a method for producing a positive electrode active material used in a liquid battery is shown.

[0038] Figure 2A The cross-sectional shape of a spherical particle having a hollow single-layer structure is schematically shown.

[0039] Figure 2B The cross-sectional shape of a spherical particle having a hollow multilayer structure is schematically shown.

[0040] Figure 2C The cross-sectional shape of a spherical particle having a hollow multilayer structure is schematically shown.

[0041] Figure 3 An example of a battery configuration is schematically shown.

[0042] Figure 4 The cross-sectional shapes of positive electrode active materials A to D are shown.

[0043] Description of Reference Numerals

[0044] 100 Batteries (solid batteries, liquid batteries)

[0045] 10 Positive electrode active material layer

[0046] 20 Electrolyte layer

[0047] 30 Negative electrode active material layer

[0048] 40 positive electrode collector

[0049] 50 Negative electrode collector DETAILED DESCRIPTION

[0050] 1. First option

[0051] The positive electrode active material according to the first embodiment is used for a solid battery.

[0052] 1.1 Method for manufacturing positive electrode active material for solid battery

[0053] like Figure 1A As shown, the method for manufacturing a positive electrode active material for a solid battery includes:

[0054] S1: Obtaining oxide particles containing Na having a P2 type structure; and

[0055] S2: At least a portion of Na in the above-mentioned Na-containing oxide particles is ion-exchanged with Li to obtain Li-containing oxide particles having an O2 type structure.

[0056] The oxide particles containing Na are spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm. Figure 2A As shown, the Li-containing oxide particles are spherical particles having a hollow single-layer structure.

[0057] In the present application, the "average particle size" refers to the particle size at 50% of the cumulative value in the volume-based particle size distribution using a laser diffraction / scattering method (D50, median diameter), unless otherwise specified.

[0058] In this application, the so-called "spherical particles" refer to particles with a circularity of 0.80 or more. The circularity of spherical particles can be 0.81 or more, 0.82 or more, 0.83 or more, 0.84 or more, 0.85 or more, 0.86 or more, 0.87 or more, 0.88 or more, 0.89 or more, or 0.90 or more. The circularity of the particles is 4πS / L 2Definition. Wherein, S is the orthographic projection area of ​​the particle, and L is the perimeter of the orthographic projection image of the particle. The circularity of the particle can be obtained by observing the appearance or cross-sectional shape of the particle using a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an optical microscope. In the case of being composed of a plurality of particles, the circularity is measured as an average value, for example, as described below.

[0059] (1) First, the particle size distribution of the particles is measured. Specifically, the particle size at 10% cumulative value (D10) and the particle size at 90% cumulative value (D90) in the volume-based particle size distribution are determined by laser diffraction / scattering method.

[0060] (2) For the observation of particles for measuring particle size distribution, SEM, TEM, or optical microscope is used to observe the image, and 100 particles having a circle equivalent diameter (the diameter of a circle having the same area as the orthographic projection area of ​​the particle) greater than D10 and less than D90 determined in (1) are randomly extracted from the particles contained in the image.

[0061] (3) The circularity of each of the 100 extracted particles is calculated using image processing, and the average value is regarded as the "circularity of the particles".

[0062] 1.1.1S1

[0063] In S1, Na-containing oxide particles having a P2 type structure are obtained. The Na-containing oxide particles obtained in S1 are spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm.

[0064] Spherical oxide particles containing Na that have a P2 type structure and a predetermined average particle size can be produced, for example, through the following S1-1, S1-2, and S1-3.

[0065] S1-1: Obtaining precursor particles

[0066] S1-2: The surface of the above-mentioned precursor particles is coated with a Na source to obtain composite particles

[0067] S1-3: sintering the composite particles

[0068] In S1-1, precursor particles are obtained. The precursor particles, for example, contain at least one element of Mn, Ni and Co. The precursor particles may contain at least Mn, and one or both selected from Ni and Co, and may contain at least Mn, Ni and Co. The precursor particles may be a salt containing at least one element of Mn, Ni and Co. For example, the precursor particles may be at least one of carbonates, sulfates, nitrates and acetates. Alternatively, the precursor particles may be a compound other than a salt. For example, the precursor particles may be a hydroxide. The precursor particles may be a hydrate. The precursor particles may be a combination of multiple compounds. The precursor particles are spherical particles. The size of the precursor particles is determined according to the average particle size of the target oxide particles containing Na.

[0069] In S1-1, an ion source that can form a precipitate with transition metal ions in an aqueous solution and a transition metal compound containing at least one element of Mn, Ni and Co can be used, and a coprecipitation method (coprecipitation method) can be used to obtain a precipitate as the above-mentioned precursor particles. Thus, spherical particles as precursor particles are obtained. "Ion source that can form a precipitate with transition metal ions in an aqueous solution" can be, for example, at least one selected from sodium salts such as sodium carbonate and sodium nitrate, sodium hydroxide, and sodium oxide. The transition metal compound can be the above-mentioned salt or hydroxide containing at least one element of Mn, Ni and Co. Specifically, in S1-1, after the ion source and the transition metal compound are made into solutions respectively, each solution is dripped and mixed, thereby obtaining a precipitate as a precursor particle. At this time, as a solvent, for example, water is used. At this time, as a base, various sodium compounds can be used, and in addition, an ammonia solution can be added to adjust the alkalinity. In the case of the coprecipitation method, for example, an aqueous solution of a transition metal compound and an aqueous solution of sodium carbonate can be prepared, and each aqueous solution can be dripped and mixed to obtain a precipitate as a precursor particle. Alternatively, the precursor particles can also be obtained by a sol-gel method. In particular, spherical particles as precursor particles can be obtained efficiently by a coprecipitation method.

[0070] In S1-1, the precursor particles may contain element M. Element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W. These elements M, for example, have the function of stabilizing the P2 type structure and the O2 type structure. There is no particular limitation on the method for obtaining the precursor particles containing element M. In the case where the precursor particles are obtained by the coprecipitation method in S1-1, for example, an aqueous solution of a transition metal compound containing at least one of Mn, Ni and Co, an aqueous solution of sodium carbonate, and an aqueous solution of a compound of element M can be prepared, and each aqueous solution can be dripped and mixed to obtain a precursor containing at least one of Mn, Ni and Co and also containing element M. Alternatively, element M may not be added in S1-1, and element M may be doped during the Na doping sintering in S1-2 and S1-3 described later.

[0071] In S1-2, the surface of the precursor particles obtained by S1-1 is coated with a Na source to obtain composite particles. The Na source can be a salt containing Na such as carbonates and nitrates, or a compound other than salts such as sodium oxide and sodium hydroxide. In S1-2, the amount of the Na source coated on the surface of the precursor particles can be determined by adding the portion of Na that disappears during subsequent calcination.

[0072] In S1-2, there is no particular limitation on the coverage of the Na source relative to the surface of the precursor particles. For example, in S1-2, the above-mentioned composite particles can be obtained by covering the surface of the above-mentioned precursor particles with a Na source by more than 40 area%, more than 50 area%, more than 60 area% or more than 70 area%. Here, in the case where the precursor obtained by S1-1 is a spherical particle and the composite particles obtained by S1-2 are obtained by covering more than 40 area% of the surface of the precursor particles with the Na source, in S1-3 described later, the oxide particles containing Na with a P2 type structure tend to become spherical particles. If the coverage of the Na source is small, then when the composite particles are fired, P2 type crystals (P2 type crystals) tend to grow abnormally on the surface of the composite particles, and the oxide particles containing Na tend to become plate-like particles. In the case where the coverage of the Na source is large, when the composite particles are fired, the crystallites of the P2 type crystals tend to become smaller, and the oxide particles containing Na tend to become spherical particles corresponding to the shape of the precursor particles.

[0073] In S1-2, the method for coating the surface of the above-mentioned precursor particles with a Na source is not particularly limited. As mentioned above, when more than 40 area % of the surface of the precursor particles are coated with a Na source, various methods can be cited as the method. For example, a tumbling flow coating method and a spray drying method can be cited. That is, a coating solution having dissolved Na source is prepared, and the coating solution is dried while or after contacting the surface of the precursor particles. By adjusting the conditions (temperature, time, number of times, etc.) of the coating, more than 40 area % of the surface of the precursor particles can be coated with a Na source.

[0074] In S1-2, the precursor particles may be coated with an M source and a Na source. For example, in S1-2, the precursor particles obtained by S1-1, the Na source, and the M source containing at least one element M selected from B, Mg, Al, K, Ca, Ti, V, Cr, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W may be mixed to obtain composite particles. The M source may be, for example, a salt containing the element M such as a carbonate or a sulfate, or a compound other than a salt such as an oxide or a hydroxide. The amount of the M source relative to the precursor particles may be determined according to the chemical composition of the oxide particles containing Na after sintering.

[0075] In S1-3, the composite particles obtained in S1-2 are fired to obtain an oxide containing Na having a P2 type structure. S1-3 may include, for example, the following S1-3-1, S1-3-2, and S1-3-3.

[0076] S1-3-1: The composite particles are subjected to preliminary calcination at a temperature of 300° C. or higher and lower than 700° C. for a period of 2 hours or higher and 10 hours or lower.

[0077] S1-3-2: Following the preliminary calcination, the composite particles are subjected to main calcination at a temperature of 700° C. to 1100° C. for 30 minutes to 48 hours.

[0078] S1-3-3: Following the main calcination, the composite particles are heated from a temperature T above 200°C to 1快速 Cool to a temperature T2 below 100°C.

[0079] In S1-3-1, the composite particles are pre-calcined at a temperature of 300°C to 700°C for 2 hours to 10 hours. In S1-3-1, the composite particles may be pre-calcined after being optionally molded. The pre-calcination is performed at a temperature lower than that of the main calcination. By sufficiently pre-calcining, the P2 phase can be appropriately generated in the main calcination, and the generation of crystalline phases other than the P2 phase can be suppressed. That is, in S1-3-1, by setting the pre-calcination temperature to 300°C to 700°C and the pre-calcination time to 2 hours to 10 hours, the composite particles can be sufficiently pre-calcined, and in the oxide particles containing Na obtained by S1-3-2 and S1-3-3 described later, the P2 phase can be appropriately generated while suppressing the generation of phases other than the P2 phase. Thus, the oxide particles containing Li obtained by S2 have an O2-type structure, a hollow single-layer structure, and are spherical. The pre-firing temperature may be 400° C. to less than 700° C., 450° C. to less than 700° C., 500° C. to less than 700° C., 550° C. to less than 700° C., or 550° C. to 650° C. In addition, the pre-firing time may be 2 hours to 8 hours, 3 hours to 8 hours, 4 hours to 8 hours, 5 hours to 8 hours, or 5 hours to 7 hours. The pre-firing atmosphere is not particularly limited, and may be, for example, an oxygen-containing atmosphere.

[0080] In S1-3-2, following the above-mentioned pre-calcination, the main calcination is carried out for more than 30 minutes and less than 48 hours for the composite particles at a temperature of more than 700°C and less than 1100°C. In S1-3-2, the main calcination temperature of the composite particles is more than 700°C and less than 1100°C, preferably more than 800°C and less than 1000°C. If the main calcination temperature is too low, the P2 phase is not generated. If the main calcination temperature is too high, the O3 phase is easily generated instead of the P2 phase. There is no particular limitation on the heating conditions from the pre-calcination temperature to the main calcination temperature. The main calcination time can be more than 30 minutes and less than 48 hours as described above. However, the main calcination time can be used to control the shape of the oxide particles containing Na. As described above, when the coverage of the Na source in the composite particles is 40 area% or more, when the composite particles are calcined, small P2-type crystals are easily formed on their surfaces. In S1-3-2, by interconnecting one P2 type microcrystal with another P2 type microcrystal, the P2 type crystal is grown along the surface of the particle, so that the shape of the oxide particles containing Na becomes a shape corresponding to the shape of the precursor particles. For example, when the precursor particles are spherical particles, the oxide particles containing Na also become spherical particles. If the main firing time is too short, the generation of the P2 phase becomes insufficient. On the other hand, if the main firing time is too long, the P2 phase grows excessively, and the oxide particles containing Na become plate-like particles instead of spherical particles. According to the inventors, when the main firing time is more than 30 minutes and less than 3 hours, spherical particles of oxide particles containing Na are easily obtained. The oxide particles containing Na obtained after the main firing have multiple microcrystals on the surface, and may have a structure in which the microcrystals are connected.

[0081] In S1-3-3, following the above-mentioned main calcination, the above-mentioned composite particles (P2 type particles) after the main calcination are rapidly cooled (cooled at a temperature drop rate of 20°C / min or more) from a temperature T1 of more than 200°C to a temperature T2 of less than 100°C. The above-mentioned preliminary calcination and main calcination are performed, for example, in a heating furnace. In step S1-3-3, for example, after the main calcination of the composite particles in a heating furnace, the heating furnace is cooled to an arbitrary temperature T1 of more than 200°C. After reaching the temperature T1, the calcined product is taken out of the heating furnace and rapidly cooled outside the furnace to an arbitrary temperature T2 of less than 100°C. Temperature T1 is any temperature of more than 200°C, and can be any temperature of more than 250°C. Temperature T2 is any temperature of less than 100°C, and can be any temperature of less than 50°C, and can be the cooling end temperature. Between temperature T1 and temperature T2, moisture easily penetrates into the interlayers of the P2 type structure due to atomic vibration or molecular motion. It is believed that by making the time of the temperature region where water easily penetrates into the composite particles (P2 type particles) after the main sintering short (i.e., rapid cooling) when cooling the composite particles after the main sintering, the amount of water penetrating into the interlayer of the P2 type structure is reduced. In this regard, in step S1-3-3, when cooling the composite particles after the main sintering, the temperature is cooled from any temperature T1 above 200°C to any temperature T2 below 100°C outside the furnace (e.g., in a dry atmosphere outside the furnace), so that the cooling rate from temperature T1 to temperature T2 becomes high (e.g., 20°C / min or more), and it is difficult for water to penetrate into the interlayer of the P2 type structure, and the collapse of the P2 type structure can be suppressed. As a result, Na can be efficiently ion-exchanged for Li in S2 described later, and the oxide particles containing Li obtained through S2 have an O2 type structure, a hollow single-layer structure, and become spherical particles.

[0082] By the above method, spherical oxide particles containing Na and having a P2 type structure are obtained.

[0083] The oxide particles containing Na have at least a P2-type structure (belonging to the space group P63mc) as a crystal structure. The oxide particles containing Na may have a crystal structure other than the P2-type structure while having the P2-type structure. As a crystal structure other than the P2-type structure, for example, various crystal structures formed when Na is inserted into the P2-type structure or when Na is separated from the P2-type structure can be listed. The oxide particles containing Na may have a P2-type structure as a main phase.

[0084] The oxide particles containing Na, for example, contain at least one element of Mn, Ni and Co, Na and O as constituent elements. In particular, when at least Na, Mn, at least one selected from Ni and Co, and O are contained as constituent elements, and further, when at least Na, Mn, Ni, Co, and O are contained as constituent elements, the performance of the positive electrode active material obtained by S2 described below is likely to be further improved. The oxide particles containing Na may have a composition composed of Na c Mn x-p Ni y-q Co z-r M p+q+rThe chemical composition represented by O2. Wherein, 0<c≤1.00, x+y+z=1, and 0≤p+q+r<0.17. In addition, M is an element selected from at least one of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W. In the case where the oxide particles containing Na have such a chemical composition, it is easy to further maintain the P2 type structure. In the above chemical composition, c is greater than 0, and can be greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40, greater than 0.50 or greater than 0.60, and can be less than 1.00, less than 0.90, less than 0.80 or less than 0.70. x is 0 or more, and may be 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, or 0.50 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less. In addition, y is 0 or more, and may be 0.10 or more, or 0.20 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, 0.30 or less, or 0.20 or less. In addition, z is 0 or more, and may be 0.10 or more, 0.20 or more, or 0.30 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less. Element M has a small contribution to charge and discharge. In this regard, in the above-mentioned chemical composition, by p+q+r being less than 0.17, it is easy to ensure a high charge and discharge capacity. p+q+r may be less than 0.16, less than 0.15, less than 0.14, less than 0.13, less than 0.12, less than 0.11 or less than 0.10. On the other hand, by including the element M, the P2 type structure and the O2 type structure are easily stabilized. In the above-mentioned chemical composition, p+q+r is greater than 0, and may be greater than 0.01, greater than 0.02, greater than 0.03, greater than 0.04, greater than 0.05, greater than 0.06, greater than 0.07, greater than 0.08, greater than 0.09 or greater than 0.10. The composition of O is approximately 2, but is not limited to exactly 2.0 and is variable.

[0085] In the first scheme, in S2 described later, as oxide particles containing Na, spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm are used. For example, as described above, spherical oxide particles containing Na can be produced by using spherical precursor particles to make composite particles, and adjusting the sintering conditions of the composite particles. Among them, by using precursor particles having an average particle size of less than 3.5 μm and being spherical, spherical oxide particles containing Na having an average particle size of 1.0 μm or more and less than 3.5 μm and being spherical can be obtained. Alternatively, after spherical oxide particles containing Na are produced using precursor particles having irregular (random) sizes, air flow classification, screening, etc. can be performed to recover spherical oxide particles containing Na having an average particle size of 1.0 μm or more and less than 3.5 μm.

[0086] The average particle size of the oxide particles containing Na is 1.0 μm or more and less than 3.5 μm, and may be 1.2 μm or more and 3.3 μm or less, or 1.4 μm or more and 3.0 μm or less. The average particle size of the oxide particles containing Na is 1.0 μm or more and less than 3.5 μm, and the oxide particles containing Li obtained by S2 described later become particles having a hollow single-layer structure. If the oxide particles containing Na are too small, a hollow structure cannot be obtained in the oxide particles containing Li.

[0087] 1.1.2S2

[0088] In S2, at least a portion of Na in the Na-containing oxide particles obtained in S1 is ion-exchanged with Li to obtain Li-containing oxide particles having an O2 type structure. The Li-containing oxide particles obtained in S2 are spherical particles having a hollow single-layer structure.

[0089] In S2, there are methods such as using an aqueous solution containing lithium halide, and methods using a mixture of lithium halide and other lithium salts (such as molten salt) in ion exchange. From the viewpoint that the P2 type structure is easily destroyed by the intrusion of water and the viewpoint of crystallinity, in the above two methods, the method using molten salt is preferred. That is, by mixing the above-mentioned oxide particles containing Na with the P2 type structure with the molten salt, heating to a temperature above the melting point of the molten salt, it is possible to replace at least a portion of the Na of the oxide particles containing Na with Li by ion exchange.

[0090] In S2, the lithium halide constituting the molten salt is preferably at least one of lithium chloride, lithium bromide and lithium iodide. The other lithium salt constituting the molten salt is preferably lithium nitrate. By using the molten salt, the melting point is lowered compared to the case of using lithium halide or other lithium salts alone, and ion exchange at a lower temperature can be performed.

[0091] In S2, the temperature during ion exchange can be, for example, above the melting point of the above-mentioned molten salt, and below 600° C., below 500° C., below 400° C., or below 300° C. If the temperature during ion exchange is too high, an O3 type structure as a stable phase is easily generated instead of an O2 type structure. On the other hand, from the viewpoint of shortening the time spent on ion exchange, the temperature during ion exchange is preferably as high as possible.

[0092] In S2, by exchanging at least a portion of the Na of the spherical oxide particles containing Na with Li, the Na with a large ionic radius is replaced with Li with a small ionic radius, and the interlayer distance in the crystal structure is shortened and contraction occurs. Through the contraction during such ion exchange, voids are generated inside the particles. It is believed that when the size of the oxide particles containing Na is small, due to this contraction, voids are generated in the central part of the particles, resulting in a hollow single-layer structure. On the other hand, it is believed that when the size of the oxide particles containing Na is large, due to this contraction, cracks are generated in the circumferential direction inside the particles, resulting in a large number of "shells", resulting in a hollow multilayer structure described later. Furthermore, when the oxide particles containing Na are in a shape other than a sphere, uniform contraction does not occur inside the particles, and a suitable hollow structure cannot be obtained.

[0093] By using the above method, Li-containing oxide particles having an O2-type structure, a hollow single-layer structure, spherical particles, and an average particle size of 1.0 μm or more and less than 3.5 μm can be obtained. The Li-containing oxide particles can be used as a positive electrode active material for a solid battery.

[0094] 1.2 Positive electrode active materials used in solid batteries

[0095] The first embodiment relates to a positive electrode active material for a solid battery comprising oxide particles containing Li. The oxide particles containing Li have an O2 type structure. Figure 2A As shown in FIG. 1 , the Li-containing oxide particles are spherical particles having a hollow single-layer structure. In addition, the Li-containing oxide particles have an average particle size of 1.0 μm or more and less than 3.5 μm.

[0096] 1.2.1 Crystal structure

[0097] The Li-containing oxide particles involved in the first embodiment have at least an O2-type structure (belonging to the space group P63mc) as a crystal structure. The Li-containing oxide particles involved in one embodiment may have a crystal structure other than the O2-type structure while having the O2-type structure. As a crystal structure other than the O2-type structure, for example, a T#2-type structure (belonging to the space group Cmca) formed when Li is inserted into the O2-type structure or Li is separated from the O2-type structure, an O6-type structure (belonging to the space group R-3m, the c-axis length is greater than 2.5nm and less than 3.5nm, typically greater than 2.9nm and less than 3.0nm, and is different from the O3-type structure belonging to the space group R-3m), etc. The Li-containing oxide particles involved in one embodiment may have an O2-type structure as the main phase. The Li-containing oxide particles involved in one embodiment may have a structure other than the O2-type structure (for example, an O6-type structure) as the main phase. For the Li-containing oxide particles, the crystal structure that becomes the main phase may change according to its charge and discharge state.

[0098] 1.2.2 Microcrystals

[0099] The Li-containing oxide particles involved in the first scheme may be polycrystalline with multiple crystallites. For example, with respect to the Li-containing oxide particles involved in one embodiment, the surface thereof may be composed of multiple crystallites. In other words, the Li-containing oxide particles may have multiple structures connecting the crystallites on their surface. In the case where the surface of the Li-containing oxide particles is composed of multiple crystallites, there are grain boundaries on the surface. Here, the grain boundaries sometimes become the entrance and exit of the intercalation. That is, in the case where the Li-containing oxide particles are polycrystalline with multiple crystallites, the effects of increasing the entrance and exit of the intercalation and reducing the reaction resistance can be expected; the effect of shortening the moving distance of lithium ions and reducing the diffusion resistance; the effect of reducing the absolute amount of expansion and contraction during charging and discharging and making it difficult to produce cracks, etc. It is believed that the size of the crystallites can be large or small. When the size of the crystallites is small, the crystal boundaries increase, and it is easy to exert the above-mentioned favorable effects. For example, if the diameter of the crystallites constituting the Li-containing oxide particles is less than 1 μm, it is easy to obtain higher performance. In addition, "crystals" and "diameter of crystallites" can be obtained by observing the surface of the Li-containing oxide particles using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). That is, when observing the surface of the oxide particles containing Li, a closed area surrounded by grain boundaries is observed, and the area is regarded as a "crystal". For the crystallite, the maximum Feret diameter is obtained and regarded as the "diameter of the crystallite". Alternatively, the diameter of the crystallite can also be obtained by EBSD or XRD. For example, the diameter of the crystallite can be obtained based on the Scherrer formula from the half-maximum full width of the diffraction line of the XRD pattern. If the diameter of the crystallite determined by any method of the oxide particles containing Li is less than 1 μm, it is easy to exert higher performance. The crystallites constituting the oxide particles containing Li may have a first surface exposed on the surface of the particle, and the first surface may be planar. That is, the surface of the oxide particles containing Li may have a structure connecting multiple planes. As described above, when manufacturing oxide particles containing Li, it is easy to obtain crystallites having a planar first surface by growing crystallites on the surface of the particles until one crystallite is connected to another crystallite.

[0100] 1.2.3 Chemical composition

[0101] The Li-containing oxide particles according to the first embodiment include, for example, at least one element of Mn, Ni, and Co, Li, and O as constituent elements. In the case where the Li-containing oxide particles include at least Li, Mn, at least one or two selected from Ni and Co, and O as constituent elements, and further, when the Li-containing oxide particles include at least Li, Mn, Ni, Co, and O as constituent elements, higher performance is likely to be obtained. The Li-containing oxide particles may have a Li-containing oxide. a Na b Mn x-p Ni y-qCo z- r M p+q+r O2 (wherein 0<a≤1.00, 0≤b≤0.20, x+y+z=1, and 0≤p+q+r<0.17, and the element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W.) A chemical composition represented by. In the case where the oxide particles containing Li have such a chemical composition, it is easy to maintain an O2 type structure. In the above chemical composition, a is greater than 0, and may be greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40, greater than 0.50 or greater than 0.60, and is less than 1.00, and may be less than 0.90, less than 0.80 or less than 0.70. In the above chemical composition, b may be greater than 0, greater than 0.01, greater than 0.02, or greater than 0.03, and may be less than 0.20, less than 0.15, or less than 0.10. In addition, x is greater than 0, may be greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40, or greater than 0.50, and is less than 1.00, and may be less than 0.90, less than 0.80, less than 0.70, less than 0.60, or less than 0.50. In addition, y is greater than 0, may be greater than 0.10, or greater than 0.20, and is less than 1.00, and may be less than 0.90, less than 0.80, less than 0.70, less than 0.60, less than 0.50, less than 0.40, less than 0.30, or less than 0.20. In addition, z is greater than 0, and may be greater than 0.10, greater than 0.20, or greater than 0.30, and is less than 1.00, and may be less than 0.90, less than 0.80, less than 0.70, less than 0.60, less than 0.50, less than 0.40, or less than 0.30. Element M contributes little to charge and discharge. In this regard, in the above-mentioned chemical composition, it is easy to ensure a high charge and discharge capacity by having p+q+r be less than 0.17. p+q+r may be less than 0.16, less than 0.15, less than 0.14, less than 0.13, less than 0.12, less than 0.11, or less than 0.10. On the other hand, by including element M, the O2 type structure is easily stabilized. In the above chemical composition, p+q+r is greater than 0, and may be greater than 0.01, greater than 0.02, greater than 0.03, greater than 0.04, greater than 0.05, greater than 0.06, greater than 0.07, greater than 0.08, greater than 0.09, or greater than 0.10. The composition of O is approximately 2, and is not limited to exactly 2.0, and is variable.

[0102] 1.2.4 Hollow single-layer structure

[0103] The Li-containing oxide particles involved in the first embodiment have a hollow single-layer structure. Figure 2AAs shown, the "hollow single-layer structure" refers to a structure in which the cross-sectional shape of the particle has a shell 1a and the inner side of the shell is hollow (void). The surface of the shell 1a can be composed of multiple crystallites, for example. In the oxide particles containing Li, the shell 1a can be composed in a manner in which multiple crystallites are connected along the periphery of the particle. The size of the crystallites constituting the shell 1a can be large or small. When the size of the crystallites is small, the grain boundaries on the surface of the particles increase, and it is easy to exert the above-mentioned favorable effects. In addition, the crystallites constituting the shell 1a may have a first surface exposed on the surface of the particle, and the first surface may be planar. For the size of the crystallites, as described above. The outer shape (peripheral shape) of the shell 1a is spherical as described above. On the other hand, the inner shape (inner shape) of the shell 1a is not particularly limited, and it can be a shape corresponding to the outer shape. However, the outer shape and inner shape of the shell 1a are not necessarily parallel to each other. Both the outer shape and the inner shape of the shell 1a may have concave and convex. In addition, the shell 1a may have voids and gaps. That is, the crystallites constituting the shell 1a may have defects such as voids and gaps. Furthermore, the shell 1a may have a thickness. The thickness of the shell 1a may be, for example, 5% or more and less than 50% of the diameter (circle-equivalent diameter in the cross-sectional shape) of the oxide particle containing Li, or 5% or more and less than 45%. The size of the voids (porosity) present inside the shell 1a is not particularly limited.

[0104] like Figure 2A As shown, the Li-containing oxide particles involved in the first embodiment can also be said to have a core-shell structure. That is, the Li-containing oxide particles involved in one embodiment may have a shell and a core (void) arranged inside the shell. The "shell" is as described above. On the other hand, the entire "core" may be voids.

[0105] 1.2.5 Spherical particles

[0106] As described above, the Li-containing oxide particles having an O2-type structure are obtained by exchanging at least a portion of the Na ions of the Na-containing oxide particles having a P2-type structure for Li. Among them, the P2-type structure is a hexagonal system, the diffusion coefficient of Na ions is large, and it is easy to crystallize and grow in a specific direction. In particular, in the case of containing at least one of Mn, Ni and Co as a transition metal element constituting the P2-type structure, it is easy to grow in a plate-like crystal in a specific direction. Therefore, in the past, as Na-containing oxide particles having a P2-type structure, only plate-like particles with a large aspect ratio and a crystal growth direction biased in a specific direction can be manufactured. As a result, for Li-containing oxide particles having an O2-type structure, only plate-like particles can be manufactured. In addition, it is believed that the plate-like growth of the P2-type structure is a principle and is inevitable. Therefore, for the previous O2-type Li-containing oxide particles, the performance as an active material is improved by controlling its chemical composition and crystal structure on the premise that it is plate-like.

[0107] And as Figure 2A As shown, the Li-containing oxide particles involved in the first scheme are spherical particles. Compared with non-spherical Li-containing oxide particles (such as the above-mentioned plate-like particles), spherical Li-containing oxide particles are easy to suppress the growth of crystallites and have the advantage that the crystallites are easy to become smaller. That is, in the case where the Li-containing oxide particles are spherical, the reaction resistance is reduced by reducing the crystallite size, and the internal diffusion resistance is easy to reduce. Furthermore, it is believed that by spheroidization, the curvature is reduced, and the lithium ion conduction resistance in the layer is reduced when applied to the positive electrode active material layer. As a result, the spherical Li-containing oxide particles have a lower resistance than the non-spherical Li-containing oxide particles, and are easy to have excellent rate characteristics.

[0108] 1.2.6 Average particle size

[0109] The Li-containing oxide particles involved in the first scheme have an average particle size of 1.0 μm or more and less than 3.5 μm. The average particle size of the Li-containing oxide particles may be 1.2 μm or more and 3.3 μm or 1.4 μm or more and 3.0 μm or less. As described above, as long as the average particle size of the Li-containing oxide particles is 1.0 μm or more and less than 3.5 μm, the Li-containing oxide particles have a hollow single-layer structure and have low resistance when applied to solid batteries. Furthermore, if the Li-containing oxide particles are too small, agglomeration between particles is likely to occur. By having an average particle size of 1.0 μm or more of the Li-containing oxide particles, such agglomeration problem is unlikely to occur.

[0110] 1.2.7 Specific surface area

[0111] There is no particular limitation on the specific surface area of ​​the Li-containing oxide particles involved in the first embodiment. However, in the case of using the Li-containing oxide particles as the positive electrode active material for solid batteries, it is believed that the smaller the specific surface area of ​​the Li-containing oxide particles, the fewer the internal voids of the Li-containing oxide particles, and the easier it is to ensure the ion conduction path. In this regard, when the Li-containing oxide particles have a hollow single-layer structure, are spherical particles, and have an average particle size of 1.0 μm or more and less than 3.5 μm, the Li-containing oxide particles have an average particle size of less than 4.5 μm. 2 When the specific surface area is 1.0 m / g, higher performance can be expected as a positive electrode active material for solid batteries. The specific surface area of ​​the Li-containing oxide particles can be 1.0 m 2 / g or more and less than 4.5m 2 / g, 2.0m 2 / g or more and 4.0m 2 / g or less, or 2.5m 2 / g or more and 3.5m 2 / g or less.

[0112] 1.2.8 Supplement

[0113] The positive electrode active material involved in the first scheme may only include the above-mentioned oxide particles containing Li, or may include positive electrode active materials other than the above-mentioned oxide particles containing Li (other positive electrode active materials) while including the above-mentioned oxide particles containing Li. From the viewpoint of further improving the effect produced by the technology disclosed in the present invention, the proportion of other positive electrode active materials in the whole positive electrode active material may be a small amount. For example, when the whole positive electrode active material is set to 100 mass%, the content of the above-mentioned oxide particles containing Li may be 50 mass% or more and 100 mass% or less, 60 mass% or more and 100 mass% or less, 70 mass% or more and 100 mass% or less, 80 mass% or more and 100 mass% or less, 90 mass% or more and 100 mass% or less, 95 mass% or more and 100 mass% or less, or 99 mass% or more and 100 mass% or less.

[0114] 1.3 Solid-state batteries

[0115] The positive electrode active material involved in the first embodiment is used as a positive electrode active material for a solid battery. The so-called "solid battery" refers to a battery containing a solid electrolyte. A solid battery may contain a liquid component while containing a solid electrolyte, or may be a full solid battery without a liquid component. In addition, as for the electrolyte contained in the solid battery, all of it may be a solid electrolyte, or it may be a combination of a solid electrolyte and a liquid electrolyte. Figure 3 As shown, a solid battery 100 according to one embodiment includes a positive electrode active material layer 10, an electrolyte layer 20, and a negative electrode active material layer 30. The positive electrode active material layer 10 includes the positive electrode active material according to the first embodiment described above. In addition, the positive electrode active material layer 10 includes a solid electrolyte.

[0116] 1.3.1 Positive electrode active material layer

[0117] The positive electrode active material layer 10 contains at least the positive electrode active material and solid electrolyte involved in the above-mentioned first embodiment, and may further optionally contain other electrolytes, conductive additives and binders. Furthermore, the positive electrode active material layer 10 may also contain various additives. The content of each of the positive electrode active material, electrolyte, conductive additive and binder in the positive electrode active material layer 10 can be appropriately determined according to the target battery performance. For example, when the positive electrode active material layer 10 as a whole (solid component as a whole) is set to 100% by mass, the content of the positive electrode active material may be 40% by mass or more, 50% by mass or more, or 60% by mass or less, and may be 100% by mass or less or 90% by mass or less. There is no particular limitation on the shape of the positive electrode active material layer 10, for example, it may be a sheet-shaped positive electrode active material layer 10 having a substantially flat surface. There is no particular limitation on the thickness of the positive electrode active material layer 10, for example, it may be 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0118] 1.3.1.1 Positive electrode active material

[0119] For the positive electrode active material, as described above. That is, the positive electrode active material layer 10 includes at least the above-mentioned oxide particles containing Li as the positive electrode active material. As described above, the positive electrode active material may include only the above-mentioned oxide particles containing Li, or may include the above-mentioned oxide particles containing Li while also including positive electrode active materials other than them (other positive electrode active materials). From the viewpoint of further improving the effect of the technology disclosed in the present invention, the proportion of other positive electrode active materials in the whole positive electrode active material may be a small amount. For example, when the whole of the positive electrode active material is set to 100% by mass, the content of the above-mentioned oxide particles containing Li may be 50% by mass or more and 100% by mass or less, 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, 80% by mass or more and 100% by mass or less, 90% by mass or more and 100% by mass or less, 95% by mass or more and 100% by mass or less, or 99% by mass or more and 100% by mass or less.

[0120] As for other positive electrode active materials, all known positive electrode active materials as positive electrode active materials for solid batteries can be used. Other positive electrode active materials may be, for example, at least one selected from various lithium compounds, elemental sulfur and sulfur compounds other than the above-mentioned oxides containing Li. The lithium compound as other positive electrode active materials may be an oxide containing Li containing at least one element M, Li and O. Element M may be, for example, at least one selected from Mn, Ni, Co, Al, Mg, Ca, Sc, V, Cr, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, Bi, Fe and Ti, and may be at least one selected from Mn, Ni, Co, Al, Fe and Ti. More specifically, the oxide containing Li as other positive electrode active materials may be selected from lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel cobaltate, lithium nickel manganate, lithium cobalt manganate, lithium nickel cobalt manganate (Li 1±α Ni x Co y Mn z O 2±δ (for example, 0<x<1, 0<y<1, 0<z<1, x+y+z=1)), spinel lithium compounds (Li 1+x Mn 2-x-y M y O4 (M is one or more selected from Al, Mg, Co, Fe, Ni and Zn) represented by a different element substitution Li-Mn spinel, etc.), lithium nickel cobalt aluminum oxide (such as Li 1±α Ni p Co q Al r O 2±δ(e.g., p+q+r=1)), lithium titanate, lithium metal phosphate (LiMPO4, etc., M is one or more selected from Fe, Mn, Co and Ni), etc. In particular, when other positive electrode active materials include Li-containing oxides containing at least one of Ni, Co and Mn, Li and O as constituent elements, the performance of the battery is easily further improved. Alternatively, when other positive electrode active materials include Li-containing oxides containing at least one of Ni, Co and Al, Li and O as constituent elements, the performance of the battery is easily further improved. Other positive electrode active materials may be used alone or in combination of two or more. The shape of other positive electrode active materials may be a general shape of positive electrode active materials for batteries. Other positive electrode active materials may be, for example, in the form of particles. Other positive electrode active materials may be solid, may have voids, for example, may be porous, or may be hollow. Other positive electrode active materials may be primary particles, or may be secondary particles formed by the aggregation of multiple primary particles. The average particle diameter D50 of other positive electrode active materials may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less.

[0121] 1.3.1.2 Protective layer

[0122] An ion-conductive protective layer may be formed on the surface of the positive electrode active material. That is, the positive electrode active material layer 10 may include a composite of a positive electrode active material and a protective layer, and at least a portion of the surface of the positive electrode active material in the composite may be covered with a protective layer. Thus, for example, it is easy to suppress the reaction of the positive electrode active material with other battery materials (such as the sulfide solid electrolyte described later). The ion-conductive protective layer may include various ion-conductive compounds. For example, the ion-conductive compound may be at least one selected from ion-conductive oxides and ion-conductive halides.

[0123] The ion conductive oxide may contain, for example, at least one element selected from B, C, Al, Si, P, S, Ti, La, Zr, Nb, Mo, Zn and W, Li and O. The ion conductive oxide may be an oxynitride containing N. More specifically, the ion conductive oxide may be selected from Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 At least one of Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, Li2WO4, LiPON, Li2O-LaO2, Li2O-ZnO2, etc. The ion conductive oxide may be a product in which a part of the elements is replaced by various doping elements.

[0124] The ion-conductive halide may be, for example, at least one of the various compounds exemplified as the halide solid electrolyte described later. The ion-conductive halide may contain, for example, at least one element selected from Mg, Ca, Sr, Ba, Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb, and Sm, at least one halogen element selected from Cl, Br, I, and F, and Li. The ion-conductive halide may contain at least one element selected from Ti, Al, Gd, Ca, Zr, and Y, at least one selected from Cl, Br, I, and F, and Li. In addition, the ion-conductive halide may contain at least one element selected from Ti and Al, at least one element selected from Cl, Br, I, and F, and Li. In addition, the ion-conductive halide may be, for example, a composite halide of Li and Ti and Al and F.

[0125] The coverage (area ratio) of the protective layer to the surface of the positive electrode active material may be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer may be, for example, 0.1 nm or more, 1 nm or more, or 100 nm or less, or 20 nm or less.

[0126] 1.3.1.2 Electrolytes

[0127] The positive electrode active material layer 10 includes a solid electrolyte. As a solid electrolyte, a known solid electrolyte can be used. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, the ion conductivity and heat resistance of the inorganic solid electrolyte are excellent. As an inorganic solid electrolyte, for example, oxide solid electrolytes, sulfide solid electrolytes, and ion-bound inorganic solid electrolytes can be listed. Among inorganic solid electrolytes, sulfide solid electrolytes, and further sulfide solid electrolytes containing at least Li, S, and P as constituent elements, have high performance. Alternatively, among inorganic solid electrolytes, ion-bound solid electrolytes, and further solid electrolytes containing at least Li, Y, and halogen (at least one of Cl, Br, I, and F) as constituent elements, have high performance. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be in particulate form. The average particle size (D50) of the solid electrolyte may be, for example, greater than 10 nm and less than 10 μm. The ion conductivity of the solid electrolyte at 25°C may be, for example, 1×10 -5 S / cm or more, 1×10 -4 S / cm or more, or 1×10 -3 S / cm or more. The solid electrolyte may be used alone or in combination of two or more.

[0128] The oxide solid electrolyte may be selected from lithium lanthanum zirconate, LiPON, Li 1+x Alx Ge 2-x One or more of (PO4)3, Li-SiO-based glass, Li-Al-SO-based glass, etc. In addition, when an oxide solid electrolyte and a liquid electrolyte are combined, ion conductivity can be improved.

[0129] The sulfide solid electrolyte may be a glass-based sulfide solid electrolyte (sulfide glass), a glass-ceramic sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. Sulfide glass is amorphous. Sulfide glass may have a glass transition temperature (Tg). In addition, when the sulfide solid electrolyte has a crystalline phase, examples of the crystalline phase include Thio-LISICON type crystalline phase, LGPS type crystalline phase, and Argentum type crystalline phase. The sulfide solid electrolyte may be in the form of particles. The average particle size (D50) of the sulfide solid electrolyte may be, for example, 10 nm or more and 100 μm or less.

[0130] The sulfide solid electrolyte may contain, for example, Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, In), and S element. In addition, the sulfide solid electrolyte may further contain at least one of O element and halogen element. In addition, the sulfide solid electrolyte may contain S element as the main component of the anion element.

[0131] The sulfide solid electrolyte can be, for example, selected from Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-ZmSn (wherein m and n are positive numbers. Z is any one of Ge, Zn, and Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers. M is any one of P, Si, Ge, B, Al, Ga, and In.)

[0132] There is no particular limitation on the composition of the sulfide solid electrolyte, and examples thereof include xLi2S·(100-x)P2S5(70≤x≤80), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.7≤x≤0.8, 0≤y≤30, 0≤z≤30), etc. Alternatively, the sulfide solid electrolyte may have a general formula: Li 4-x Ge 1-x P x The composition represented by S4 (0<x<1). In the above general formula, at least a part of Ge can be replaced by at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. In the above general formula, at least a part of P can be replaced by at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. In the above general formula, a part of Li can be replaced by at least one of Na, K, Mg, Ca and Zn. In the above general formula, a part of S can be replaced by halogen (at least one of F, Cl, Br and I). Alternatively, the sulfide solid electrolyte may have a Li 7-a PS 6-a X a (X is at least one of Cl, Br and I, and a is a number greater than 0 and less than 2). a may be 0 or greater than 0. In the latter case, a may be greater than 0.1, greater than 0.5, or greater than 1. In addition, a may be less than 1.8 or less than 1.5.

[0133] The ion-bound solid electrolyte may, for example, contain at least one element selected from Mg, Ca, Sr, Ba, Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb and Sm. These elements can generate cations in water. In addition, the ion-bound solid electrolyte material may, for example, further contain at least one halogen element selected from Cl, Br, I and F. These elements can generate anions in water. The ion-bound solid electrolyte may contain at least one selected from Gd, Ca, Zr and Y, at least one selected from Cl, Br, I and F, and Li. In addition, the ion-bound solid electrolyte contains Li and Y, and may contain at least one selected from Cl, Br, I and F. More specifically, the ion-bound solid electrolyte may contain Li and Y and Cl and Br, may contain Li and Ca and Y and Gd and Cl and Br, or may contain Li and Zr and Y and Cl. More specifically, the ion-bound solid electrolyte may be Li3YBr2Cl4, Li 2.8 Ca 0.1 Y 0.5 G 0.5 Br2Cl4, and Li 2.5 Y 0.5 Zr0.5 At least one of Cl6.

[0134] The ion-binding solid electrolyte may be a halide solid electrolyte, which has excellent ion conductivity. As a halide solid electrolyte, for example, it may have a composition represented by formula (A):

[0135] Li α M β X γ ···(A).

[0136] Wherein, α, β and γ are each independently a value greater than 0, M is at least one selected from metal elements and semi-metal elements other than Li, and X is at least one selected from Cl, Br and I. Furthermore, the "semi-metal element" may be at least one selected from B, Si, Ge, As, Sb and Te. In addition, the "metal element" may include (i) all elements contained in the first to twelfth groups of the periodic table (however, excluding hydrogen) and (ii) all elements contained in the thirteenth to sixteenth groups of the periodic table (however, excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se.). The metal element forms an inorganic compound together with the halide ion and can become a cation.

[0137] In formula (A), M may include Y (ie, yttrium). The halide solid electrolyte including Y may have a a Me b Y c A composition represented by X6 (wherein a+mb+3c=6, c>0, Me is at least one selected from metal elements and semi-metal elements other than Li and Y, and m is the valence of Me). Me can be, for example, at least one selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta and Nb.

[0138] The halide solid electrolyte may have a structure represented by formula (A1): Li 6-3d Y d The composition represented by X6. In formula (A1), X is one or more elements selected from Cl, Br and I. d may satisfy 0<d<2, and may be d=1. The halide solid electrolyte may have a composition represented by formula (A2): Li 3-3δ Y 1+δ The composition represented by Cl6. In formula (A2), 0<δ≤0.15. The halide solid electrolyte may have a composition represented by formula (A3): Li 3-3δ Y 1+δ The composition represented by Br6. In formula (A3), 0<δ≤0.25 may be satisfied. The halide solid electrolyte may have a composition represented by formula (A4): Li 3-3δ+a Y 1+δ-a Mea Cl 6-x-y Br x I y In formula (A4), Me may be at least one selected from Mg, Ca, Sr, Ba and Zn. In formula (A4), for example, -1<δ<2, 0<a<3, 0<(3-3δ+a), 0<(1+δ-a), 0≤x≤6, 0≤y≤6 and (x+y)≤6 are satisfied. The halide solid electrolyte may have a composition represented by formula (A5): Li 3-3δ Y 1+δ-a Me a Cl 6-x-y Br x I y In formula (A5), Me may be at least one selected from Al, Sc, Ga and Bi. In formula (A5), -1<δ<1, 0<a<2, 0<(1+δ-a), 0≤x≤6, 0≤y≤6, and (x+y)≤6. The halide solid electrolyte may have a composition represented by formula (A6): Li 3-3δ- a Y 1+δ-a Me a Cl 6-x-y Br x I y In formula (A6), Me may be at least one selected from Zr, Hf and Ti. In formula (A6), -1<δ<1, 0<a<1.5, 0<(3-3δ-a), 0<(1+δ-a), 0≤x≤6, 0≤y≤6, and (x+y)≤6. The halide solid electrolyte may have a composition represented by formula (A7): Li 3-3δ-2a Y 1+δ-a Me a Cl 6-x-y Br x I y The composition represented by the formula (A7) is: Me is at least one selected from Ta and Nb. In the formula (A7), -1<δ<1, 0<a<1.2, 0<(3-3δ-2a), 0<(1+δ-a), 0≤x≤6, 0≤y≤6, and (x+y)≤6.

[0139] The ion-bound solid electrolyte may be a complex hydride solid electrolyte. The complex hydride solid electrolyte may be composed of Li ions and complex ions containing H. The complex ions containing H may, for example, have an element M containing at least one of a non-metallic element, a semi-metallic element, and a metal element, and H bound to the element M. In addition, in the case of the complex ion containing H, the element M as the central element and the H surrounding the element M may be bound to each other via covalent bonds. In addition, the complex ion containing H may be composed of (M m H n )α- In this case, m is an arbitrary positive number, and n and α can be any positive number according to m, the valence of the element M, etc. The element M can be a non-metallic element or a metal element that can form a complex ion. For example, the element M can contain at least one of B, C and N as a non-metallic element, and can contain B. In addition, for example, the element M can contain at least one of Al, Ni and Fe as a metal element. In particular, in the case where the complex ion contains B, or in the case where the complex ion contains C and B, it is easy to ensure higher ion conductivity. As a specific example of a complex ion containing H, (CB9H 10 ) - , (CB 11 H 12 ) - ,(B 10 H 10 ) 2- ,(B 12 H 12 ) 2- 、(BH4) - 、(NH2) - 、(AlH4) - , and combinations thereof. In particular, when using (CB9H 10 ) - , (CB 11 H 12 ) - , or a combination thereof, it is easy to ensure higher ion conductivity. That is, the complex hydride solid electrolyte may contain Li, C, B and H.

[0140] The positive electrode active material layer 10 may or may not contain a liquid electrolyte (electrolyte). The electrolyte is a liquid containing lithium ions as carrier ions. The electrolyte may be an aqueous electrolyte or a non-aqueous electrolyte. The composition of the electrolyte may be the same as a known composition. The electrolyte may be a product of dissolving a lithium salt in water or a non-aqueous solvent. As a non-aqueous solvent, for example, various carbonate-based solvents can be listed. As a lithium salt, for example, lithium amide salt, LiPF6, etc. can be listed.

[0141] 1.3.1.3 Conductive additives

[0142] As the conductive aid that can be contained in the positive electrode active material layer 10, for example, carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), Ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, titanium, aluminum, and stainless steel can be listed. The conductive aid can be, for example, in the form of particles or fibers, and there is no particular limitation on the size. The conductive aid can be used alone or in combination of two or more.

[0143] 1.3.1.4 Adhesives

[0144] As the binder that can be contained in the positive electrode active material layer 10, for example, butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, etc. can be listed. Only one type of binder can be used alone, or two or more types can be used in combination.

[0145] 1.3.1.5 Others

[0146] The positive electrode active material layer 10 may contain various additives in addition to the above-mentioned components, such as a dispersant, a lubricant, and the like.

[0147] 1.3.2 Electrolyte layer

[0148] The electrolyte layer 20 is arranged between the positive electrode active material layer 10 and the negative electrode active material layer 30. The electrolyte layer 20 may include one or both of a solid electrolyte and an electrolyte solution. The electrolyte layer 20 may further optionally include a binder, etc. There is no particular limitation on the content of the electrolyte and the binder, etc. in the electrolyte layer 20. Alternatively, the electrolyte layer 20 may have a separator (diaphragm) for preventing the positive electrode active material layer 10 from contacting the negative electrode active material layer 30 while retaining the electrolyte. There is no particular limitation on the thickness of the electrolyte layer 20, for example, it may be 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0149] The electrolyte layer 20 may be composed of one layer or a plurality of layers. For example, the electrolyte layer 20 may include a first layer disposed on the positive electrode active material layer 10 side and a second layer disposed on the negative electrode active material layer 30 side, the first layer may include a first electrolyte, and the second layer may include a second electrolyte. The first electrolyte and the second electrolyte may be different types from each other. The first electrolyte and the second electrolyte may each be at least one selected from the above-mentioned oxide solid electrolyte, sulfide solid electrolyte and ion-bound solid electrolyte. For example, the first layer may include an ion-bound solid electrolyte, and the second layer may include at least one of an ion-bound solid electrolyte and a sulfide solid electrolyte.

[0150] The electrolyte contained in the electrolyte layer 20 can be appropriately selected from the electrolytes (solid electrolytes and / or liquid electrolytes) exemplified as the electrolytes that can be contained in the above-mentioned positive electrode active material layer 10. In addition, for the binder that can be contained in the electrolyte layer 20, it can be appropriately selected from the binders exemplified as the binders that can be contained in the above-mentioned positive electrode active material layer 10. Electrolytes and binders can be used alone or in combination of two or more. The separator can be a known separator, for example, separators composed of resins such as polyethylene (PE), polypropylene (PP), polyester and polyamide can be listed. The separator can be a single-layer structure or a multi-layer structure. As a separator of a multi-layer structure, for example, a separator of a two-layer structure of PE / PP, or a separator of a three-layer structure of PP / PE / PP or PE / PP / PE can be listed. The separator can be composed of non-woven fabrics such as cellulose non-woven fabrics, resin non-woven fabrics, and glass fiber non-woven fabrics.

[0151] 1.3.3 Negative electrode active material layer

[0152] The negative electrode active material layer 30 contains at least a negative electrode active material. In addition, the negative electrode active material layer 30 may optionally contain an electrolyte, a conductive aid, a binder, and various additives. The content of each component in the negative electrode active material layer 30 can be appropriately determined according to the target battery performance. For example, when the solid content of the negative electrode active material layer 30 is set to 100% by mass, the content of the negative electrode active material may be 40% by mass or more, 50% by mass or more, 60% by mass or more, or 70% by mass or more, and may be 100% by mass or less, less than 100% by mass, 95% by mass or less, or 90% by mass or less. Alternatively, when the negative electrode active material layer 30 is set to 100% by volume, the negative electrode active material and the optional electrolyte, conductive aid, and binder may contain 85% by volume or more, 90% by volume or more, or 95% by volume or more, and the remainder may be voids or other components. The shape of the negative electrode active material layer 30 is not particularly limited, and for example, it may be a sheet with a substantially flat surface. The thickness of the negative electrode active material layer 30 is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, 10 μm or more, or 30 μm or less, or 2 mm or less, 1 mm or less, 500 μm or less, or 100 μm or less.

[0153] As for the negative electrode active material, any negative electrode active material known as a negative electrode active material for a battery can be used. Among the known active materials, various materials whose potential for absorbing and releasing lithium ions (charge and discharge potential) is lower than that of the above-mentioned positive electrode active material can be used. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, etc. can be used. Among them, when the negative electrode active material layer 30 contains Si as a negative electrode active material, the performance of the solid battery 100 is easily improved. The negative electrode active material can be used alone or in combination of two or more. The shape of the negative electrode active material can be a general shape of a negative electrode active material as a battery. For example, the negative electrode active material can be in the form of particles. The negative electrode active material particles can be primary particles or secondary particles formed by the aggregation of multiple primary particles. The average particle size (D50) of the negative electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. Alternatively, the negative electrode active material may be in the form of a sheet (foil, film) such as lithium foil. That is, the negative electrode active material layer 30 may be composed of a sheet of the negative electrode active material.

[0154] As the electrolyte that can be contained in the negative electrode active material layer 30, for example, the above-mentioned solid electrolyte, electrolyte solution or a combination thereof can be cited. The conductive aid that can be contained in the negative electrode active material layer 30 can be appropriately selected from the conductive aids exemplified as the conductive aids that can be contained in the above-mentioned positive electrode active material layer. The binder that can be contained in the negative electrode active material layer 30 can be appropriately selected from the binders exemplified as the binders that can be contained in the above-mentioned positive electrode active material layer. The electrolyte, the conductive aid, and the binder can be used alone or in combination of two or more.

[0155] 1.3.4 Positive electrode collector

[0156] like Figure 3As shown, the solid battery 100 may include a positive electrode collector 40 in contact with the positive electrode active material layer 10. As for the positive electrode collector 40, any positive electrode collector generally used as a positive electrode collector of a battery can be used. In addition, the positive electrode collector 40 may have a shape selected from at least one of foil, plate, mesh, punched metal, and foam. The positive electrode collector 40 may be composed of a metal foil or a metal mesh. In particular, the metal foil has excellent handling properties. The positive electrode collector 40 may be composed of a plurality of foils. As the metal constituting the positive electrode collector 40, at least one selected from Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, V, Mg, Pb, Ge, In, Sn, Zr, and stainless steel can be listed. In particular, from the viewpoint of ensuring oxidation resistance, the positive electrode collector 40 may contain Al. In order to adjust resistance, etc., the positive electrode collector 40 may have some coating on its surface. For example, the positive electrode current collector 40 may have a carbon coating. In addition, the positive electrode current collector 40 may be a product obtained by plating or vapor-depositing the above-mentioned metal on a metal foil or a substrate. In addition, when the positive electrode current collector 40 is composed of a plurality of metal foils, some layers may be present between the plurality of metal foils. The thickness of the positive electrode current collector 40 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or less, and may be 1 mm or less or 100 μm or less.

[0157] 1.3.5 Negative electrode collector

[0158] like Figure 3As shown, the solid battery 100 may include a negative electrode collector 50 in contact with the negative electrode active material layer 30. As for the negative electrode collector 50, any negative electrode collector generally used as a negative electrode collector of a battery can be used. In addition, the negative electrode collector 50 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, etc. The negative electrode collector 50 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, the metal foil has excellent handling properties. The negative electrode collector 50 may be composed of a plurality of foils and sheets. As the metal constituting the negative electrode collector 50, at least one selected from Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, V, Mg, Pb, Ge, In, Sn, Zr, and stainless steel can be listed. In particular, from the viewpoint of ensuring reduction resistance and the viewpoint of being difficult to alloy with lithium, the negative electrode collector 50 may contain at least one metal selected from Cu, Ni, and stainless steel. In order to adjust the resistance, etc., the negative electrode collector 50 may have some coating on its surface. For example, the negative electrode collector 50 may have a carbon coating. The negative electrode collector 50 may be an aluminum foil with a carbon coating. In addition, the negative electrode collector 50 may be a product obtained by plating or vapor-depositing the above-mentioned metal on a metal foil or a substrate. In addition, when the negative electrode collector 50 is composed of a plurality of metal foils, there may be some layers between the plurality of metal foils. There is no particular limitation on the thickness of the negative electrode collector 50. For example, it may be greater than 0.1 μm or greater than 1 μm, and may be less than 1 mm or less than 100 μm.

[0159] 1.3.6 Other components

[0160] In addition to the above-mentioned structures, the solid battery 100 may include a general structure as a battery. For example, pole pieces, terminals, etc. As for the solid battery 100, each of the above-mentioned structures can be accommodated inside the outer packaging body. As for the outer packaging body, any outer packaging body known as the outer packaging body of a battery can be adopted. In addition, a plurality of solid batteries 100 can be electrically connected arbitrarily to form a battery group, and a plurality of solid batteries 100 can be overlapped arbitrarily to form a battery group. In this case, the battery group can be accommodated inside a known battery casing. As the shape of the solid battery 100, for example, a coin type, a stacked body type, a cylindrical type, and a square type can be listed.

[0161] The solid battery 100 can be manufactured by applying a known method in addition to using the above-mentioned specific positive electrode active material. For example, it can be manufactured as follows. However, the manufacturing method of the solid battery 100 is not limited to the following method, for example, each layer can be formed by dry molding or the like.

[0162] (1) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The positive electrode layer slurry is applied to the surface of the positive electrode collector using a scraper or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode collector to prepare a positive electrode.

[0163] (2) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The negative electrode layer slurry is applied to the surface of the negative electrode collector using a scraper or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode collector to prepare a negative electrode.

[0164] (3) The layers are stacked in a manner such that the electrolyte layer (solid electrolyte layer or separator) is sandwiched between the negative electrode and the positive electrode to obtain a stack having a negative electrode collector, a negative electrode active material layer, an electrolyte layer, a positive electrode active material layer and a positive electrode collector in this order. Other components such as terminals are installed on the stack as needed.

[0165] (4) The stacked body is housed in a battery case, an optional electrolyte is filled into the battery case, and the stacked body is sealed to produce a solid battery.

[0166] 2. Second Option

[0167] The positive electrode active material according to the second embodiment is used for a liquid battery.

[0168] 2.1 Method for manufacturing positive electrode active material for liquid battery

[0169] like Figure 1B As shown, the method for manufacturing a positive electrode active material for a liquid battery includes:

[0170] S1: Obtaining oxide particles containing Na having a P2 type structure; and

[0171] S2: At least a portion of Na in the above-mentioned Na-containing oxide particles is ion-exchanged with Li to obtain Li-containing oxide particles having an O2 type structure.

[0172] The oxide particles containing Na are spherical particles having an average particle size of 3.5 μm or more. Figure 2B As shown, the Li-containing oxide particles are spherical particles having a hollow multilayer structure.

[0173] 2.1.1S1

[0174] In S1, Na-containing oxide particles having a P2-type structure are obtained. Among them, the Na-containing oxide particles obtained using S1 are spherical particles with an average particle size of 3.5 μm or more. S1 in the second scheme is the same as S1 in the first scheme except that the average particle size of the Na-containing oxide particles is different. That is, S1 in the second scheme may include the above-mentioned S1-1, S1-2 and S1-3. For example, by using precursor particles having an average particle size of 3.5 μm or more and being spherical, Na-containing oxide particles having an average particle size of 3.5 μm or more and being spherical are obtained. Alternatively, after spherical Na-containing oxide particles are manufactured using precursor particles having irregular (random) sizes, air flow classification, screening, etc. are performed to recover spherical Na-containing oxide particles having an average particle size of 3.5 μm or more.

[0175] As described above, the Na-containing oxide particles obtained by using S1 in the second scheme may be the same as the Na-containing oxide particles obtained by using S1 in the first scheme except that the average particle size is different. That is, the Na-containing oxide particles have at least a P2-type structure (belonging to the space group P63mc) as a crystal structure. The Na-containing oxide particles may have a crystal structure other than the P2-type structure while having the P2-type structure. As crystal structures other than the P2-type structure, for example, various crystal structures formed when Na is inserted into the P2-type structure or when Na is separated from the P2-type structure can be listed. The Na-containing oxide particles may have a P2-type structure as a main phase. In addition, the Na-containing oxide particles may contain, for example, at least one element of Mn, Ni and Co, Na and O as constituent elements. Among them, when at least Na, Mn, at least one selected from Ni and Co, and O are contained as constituent elements, in particular, when at least Na, Mn, Ni, Co, and O are contained as constituent elements, the performance of the positive electrode active material obtained by S2 described later is easy to be further improved. The Na-containing oxide particles may have a structure composed of Na. c Mn x-p Ni y-q Co z- r M p+q+rThe chemical composition represented by O2. Wherein, 0<c≤1.00, x+y+z=1, and 0≤p+q+r<0.17. In addition, M is an element selected from at least one of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W. In the case where the oxide particles containing Na have such a chemical composition, it is easy to further maintain the P2 type structure. In the above chemical composition, c may be greater than 0, greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40, greater than 0.50 or greater than 0.60, and may be less than 1.00, less than 0.90, less than 0.80 or less than 0.70. x is 0 or more, and may be 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, or 0.50 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less. In addition, y is 0 or more, and may be 0.10 or more, or 0.20 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, 0.30 or less, or 0.20 or less. In addition, z is 0 or more, and may be 0.10 or more, 0.20 or more, or 0.30 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less. Element M has a small contribution to charge and discharge. In this regard, in the above-mentioned chemical composition, by p+q+r being less than 0.17, it is easy to ensure a high charge and discharge capacity. p+q+r may be less than 0.16, less than 0.15, less than 0.14, less than 0.13, less than 0.12, less than 0.11 or less than 0.10. On the other hand, by including the element M, the P2 type structure and the O2 type structure are easily stabilized. In the above-mentioned chemical composition, p+q+r is greater than 0, and may be greater than 0.01, greater than 0.02, greater than 0.03, greater than 0.04, greater than 0.05, greater than 0.06, greater than 0.07, greater than 0.08, greater than 0.09 or greater than 0.10. The composition of O is approximately 2, but is not limited to exactly 2.0 and is variable.

[0176] The average particle size of the oxide particles containing Na is 3.5 μm or more. The average particle size may be 3.5 μm or more and 20.0 μm or less, 3.5 μm or more and 10.0 μm or less, or 3.5 μm or more and 5.0 μm or less. The average particle size of the oxide particles containing Na is 3.5 μm or more, and the oxide particles containing Li obtained by S2 described later have a hollow multilayer structure.

[0177] 2.1.2S2

[0178] In S2, at least a portion of Na in the Na-containing oxide particles obtained in S1 is ion-exchanged with Li to obtain Li-containing oxide particles having an O2 type structure. The Li-containing oxide particles obtained by S2 are spherical particles having a hollow multilayer structure. S2 in the second embodiment is the same as S2 in the first embodiment except that the average particle size of the Na-containing oxide particles is different.

[0179] As described above, in S2, by exchanging at least a portion of Na in the spherical oxide particles containing Na with Li, voids are generated inside the particles due to shrinkage during ion exchange. As described above, it is believed that when the size of the oxide particles containing Na is large, cracks are generated in the circumferential direction inside the particles due to this shrinkage, resulting in a large number of "shells" and a hollow multilayer structure.

[0180] By the above method, Li-containing oxide particles having an O2 type structure, a hollow multilayer structure, spherical particles, and an average particle size of 3.5 μm or more are obtained. The Li-containing oxide particles are used as a positive electrode active material for a liquid battery.

[0181] 2.2 Positive electrode active materials for liquid batteries

[0182] The positive electrode active material used in the liquid battery according to the second embodiment comprises oxide particles containing Li. The oxide particles containing Li have an O2 type structure. Figure 2B As shown, the Li-containing oxide particles are spherical particles having a hollow multilayer structure. In addition, the Li-containing oxide particles have an average particle size of 3.5 μm or more.

[0183] 2.2.1 Crystal structure, crystallites and chemical composition

[0184] The crystal structure, crystallites and chemical composition of the Li-containing oxide particles involved in the second scheme may be the same as those of the first scheme. That is, the Li-containing oxide particles involved in the second scheme have an O2 type structure, and may have other crystal structures while having the O2 type structure. In addition, the Li-containing oxide particles involved in the second scheme may be polycrystalline having multiple crystallites. In addition, the Li-containing oxide particles involved in the second scheme may contain, for example, at least one element of Mn, Ni and Co, Li, and O as constituent elements. Among them, when the Li-containing oxide particles contain at least Li, Mn, one or two selected from Ni and Co, and O as constituent elements, in particular, when they contain at least Li, Mn, Ni, Co, and O as constituent elements, higher performance is easily obtained. The Li-containing oxide particles may have a Li-containing oxide. a Na b Mnx-p Ni y-q Co z- r M p+q+r O2 (wherein 0<a≤1.00, 0≤b≤0.20, x+y+z=1, and 0≤p+q+r<0.17, and the element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W.) A chemical composition represented by. In the case where the oxide particles containing Li have such a chemical composition, it is easy to maintain an O2 type structure. In the above chemical composition, a is greater than 0, and may be greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40, greater than 0.50 or greater than 0.60, and is less than 1.00, and may be less than 0.90, less than 0.80 or less than 0.70. In the above chemical composition, b may be greater than 0, greater than 0.01, greater than 0.02, or greater than 0.03, and may be less than 0.20, less than 0.15, or less than 0.10. In addition, x is greater than 0, may be greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40, or greater than 0.50, and is less than 1.00, and may be less than 0.90, less than 0.80, less than 0.70, less than 0.60, or less than 0.50. In addition, y is greater than 0, may be greater than 0.10, or greater than 0.20, and is less than 1.00, and may be less than 0.90, less than 0.80, less than 0.70, less than 0.60, less than 0.50, less than 0.40, less than 0.30, or less than 0.20. In addition, z is greater than 0, and may be greater than 0.10, greater than 0.20, or greater than 0.30, and is less than 1.00, and may be less than 0.90, less than 0.80, less than 0.70, less than 0.60, less than 0.50, less than 0.40, or less than 0.30. Element M contributes little to charge and discharge. In this regard, in the above-mentioned chemical composition, it is easy to ensure a high charge and discharge capacity by having p+q+r be less than 0.17. p+q+r may be less than 0.16, less than 0.15, less than 0.14, less than 0.13, less than 0.12, less than 0.11, or less than 0.10. On the other hand, by including element M, the O2 type structure is easily stabilized. In the above chemical composition, p+q+r is greater than 0, and may be greater than 0.01, greater than 0.02, greater than 0.03, greater than 0.04, greater than 0.05, greater than 0.06, greater than 0.07, greater than 0.08, greater than 0.09, or greater than 0.10. The composition of O is approximately 2, but is not limited to exactly 2.0, and is variable.

[0185] 2.2.2 Hollow multilayer structure

[0186] The Li-containing oxide particles involved in the second embodiment have a hollow multilayer structure. Figure 2B As shown in FIG. 1 , the so-called “hollow multilayer structure” refers to a structure having an outer shell 1a and at least one inner shell 1b or a solid part 1c in the cross-sectional shape of the particle. Figure 2C As shown, the solid part 1c may not exist and become a gap. The Li-containing oxide particles involved in the second scheme may have multiple shells 1a, 1b, or may have an outer shell 1a and a solid part 1c. In this case, there may be gaps between at least one shell and another shell, and between the shell and the solid part. In the case where the Li-containing oxide particles have multiple shells 1a, 1b, since the outside and the inside of each shell can be in contact with the liquid, the contact area between the Li-containing oxide particles and the liquid is easily increased. For example, when the electrolyte spreads throughout the interior of the Li-containing oxide particles, the contact area between the particles and the electrolyte is easily increased. It should be noted that the so-called "having multiple shells" means that there is another shell inside a shell. Among them, one shell and another shell may be partially in contact or partially combined. However, even if there is a gap along the circumferential direction between a shell and another shell inside it, when more than 50% of the inner circumference of a shell is bonded to the outer circumference of another shell inside it, the shell and the other shell are not regarded as independent shells (multilayer), but are regarded as constituting one shell (single layer) with the shell.

[0187] In the oxide particles containing Li involved in the second scheme, the surface of the shell 1a may be composed of, for example, a plurality of crystallites. In the oxide particles containing Li, the shell 1a may be composed in a manner in which a plurality of crystallites are connected along the periphery of the particle. The size of the crystallites constituting the shell 1a may be large or small. When the size of the crystallites is small, the grain boundaries on the surface of the particles increase, and it is easy to exert a favorable effect. In addition, the crystallites constituting the shell 1a may have a first surface exposed on the surface of the particle, and the first surface may be planar. As for the size of the crystallites, as described above. The outer shape (peripheral shape) of the shell 1a is spherical as described above. On the other hand, the inner shape (inner shape) of the shell 1a is not particularly limited, and may be a shape corresponding to the outer shape. However, the outer shape and inner shape of the shell 1a are not necessarily parallel to each other. The outer shape and inner shape of the shell may both have concave and convex. In addition, the shell 1a may have voids and gaps. That is, the crystallites constituting the shell 1a may have defects such as voids and gaps. Furthermore, the shell 1a may have a thickness. The thickness of the outer shell 1a can be, for example, 5% or more and 40% or less, or 5% or more and 30% or less of the diameter (equivalent circle diameter in the cross-sectional shape) of the oxide particles containing Li. There is no particular limitation on the size of the voids (porosity) present on the inner side of the outer shell 1a. The outer shape (outer peripheral shape) of the inner shell 1b can be a shape corresponding to the inner peripheral shape of the outer shell 1a, or a shape different from the inner peripheral shape of the outer shell 1a. There is no particular limitation on the inner shape (inner peripheral shape) of the inner shell 1b, and it can be a shape corresponding to the outer shape. The outer shape and inner shape of the inner shell 1b are not necessarily parallel to each other. The outer shape and inner shape of the inner shell 1b can both have concave and convex. In addition, the inner shell 1b can have voids and gaps. That is, the microcrystals constituting the inner shell 1b can have defects such as voids and gaps. Furthermore, the inner shell 1b can have a thickness. The thickness of the inner shell 1b can be, for example, 5% to 40% or 5% to 30% of the diameter (circle-equivalent diameter in the cross-sectional shape) of the oxide particle containing Li. The shape and size of the gap between the outer shell 1a and the inner shell 1b, and the shape and size of the solid part 1c or the gap inside the inner shell 1b are not particularly limited. In addition, the porosity of the entire particle is not particularly limited.

[0188] like Figure 2BAs shown, in the Li-containing oxide particles involved in the second scheme, in the cross-sectional structure, there are gaps along the inner wall of the above-mentioned shell 1a. The gaps may exist continuously around the entire circumference of the inner wall of the shell 1a, or may exist continuously or intermittently along a portion of the inner wall of the shell 1a. For example, the gaps may exist in more than 50% of the entire circumference of the inner side of the shell 1a. There is no particular limitation on the size of the gaps. As described above, the shell may have liquid permeability, so the liquid that penetrates from the outside of the particle through the shell to the inside of the particle is filled in the gaps along the inner wall of the shell and may contact the inner wall of the shell. That is, in the case where there are gaps along the inner wall of the shell, the contact area between the particle and the liquid is likely to increase compared to the case where there are no gaps. For example, when the electrolyte spreads throughout the interior of the Li-containing oxide particles, the contact area between the particles and the electrolyte is likely to increase.

[0189] like Figure 2B As shown, the Li-containing oxide particles according to the second embodiment can be said to have a core-shell structure. That is, the Li-containing oxide particles according to one embodiment may have a shell (outer shell) and a core (inner shell or solid part, and voids) arranged inside the shell.

[0190] 2.2.3 Spherical particles

[0191] like Figure 2B As shown, the Li-containing oxide particles involved in the second scheme are spherical particles. As described above, spherical Li-containing oxide particles have the advantages of easily suppressing the growth of crystallites and easily reducing the crystallites compared to non-spherical Li-containing oxide particles. That is, in the case where the Li-containing oxide particles are spherical, the reaction resistance decreases due to the reduction in the crystallite size, and the internal diffusion resistance is easily reduced. Furthermore, it is believed that by spheroidization, the curvature is reduced, and the lithium ion conduction resistance in the layer is reduced when applied to the positive electrode active material layer. As a result, the spherical Li-containing oxide particles have a lower resistance than the non-spherical Li-containing oxide particles, and are easily particles with excellent rate characteristics.

[0192] 2.2.4 Average particle size

[0193] The Li-containing oxide particles involved in the second scheme have an average particle size of 3.5 μm or more. The average particle size of the Li-containing oxide particles may be 3.5 μm or more and 20.0 μm or less, 3.5 μm or more and 10.0 μm or less, or 3.5 μm or more and 5.0 μm or less. As described above, if the average particle size of the Li-containing oxide particles is 3.5 μm or more, the Li-containing oxide particles have a hollow multilayer structure and have excellent rate characteristics when used in liquid batteries.

[0194] 2.2.5 Specific surface area

[0195] There is no particular limitation on the specific surface area of ​​the Li-containing oxide particles involved in the second scheme. However, in the case of using as a positive electrode active material for a liquid battery, it is believed that the larger the specific surface area of ​​the Li-containing oxide particles, the greater the contact interface with the electrolyte, and the easier it is to ensure the ion conduction path. In this regard, when the Li-containing oxide particles have a hollow multilayer structure, are spherical particles, and have an average particle size of 3.5 μm or more, the Li-containing oxide particles may have a particle size of 4.5 μm or more. 2 The specific surface area of ​​the Li-containing oxide particles can be 4.5 m 2 / g or more and 10.0m 2 / g or less, 4.5m 2 / g or more and 8.0m 2 / g or less, or 4.5m 2 / g or above and 6.5m 2 / g or less.

[0196] 2.2.6 Supplement

[0197] The positive electrode active material involved in the second scheme may include only the above-mentioned oxide particles containing Li, as in the first scheme, or may include the above-mentioned oxide particles containing Li and other positive electrode active materials (other positive electrode active materials) at the same time. From the viewpoint of further improving the effect of the technology disclosed in the present invention, the proportion of other positive electrode active materials in the whole positive electrode active material may be a small amount. For example, when the whole of the positive electrode active material is set to 100% by mass, the content of the above-mentioned oxide particles containing Li may be 50% by mass or more and 100% by mass or less, 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, 80% by mass or more and 100% by mass or less, 90% by mass or more and 100% by mass or less, 95% by mass or more and 100% by mass or less, or 99% by mass or more and 100% by mass or less.

[0198] 2.3 Liquid battery

[0199] The positive electrode active material involved in the second embodiment is used as a positive electrode active material for a liquid battery. A "liquid battery" refers to a battery containing a liquid electrolyte (electrolyte). The electrolyte contained in the liquid battery may be entirely a liquid electrolyte or a combination of a liquid electrolyte and a solid electrolyte. Figure 3 The structure of a liquid battery according to one embodiment is schematically shown in FIG. Figure 3As shown, a liquid battery 100 according to one embodiment includes a positive electrode active material layer 10, an electrolyte layer 20, and a negative electrode active material layer 30. The positive electrode active material layer 10 includes the positive electrode active material according to the second embodiment described above. In addition, the positive electrode active material layer 10 includes a liquid electrolyte.

[0200] The positive electrode active material layer 10, the electrolyte layer 20, and the negative electrode active material layer 30 included in the liquid battery 100 may be the same as those included in the solid battery 100, except that the positive electrode active material involved in the second embodiment described above is used as the positive electrode active material and a liquid electrolyte is used as the electrolyte. The structure of the liquid battery 100 is relatively obvious, so a detailed description is omitted here.

[0201] 3. Vehicles

[0202] The solid battery or liquid battery disclosed in the present invention is preferably used in at least one vehicle selected from a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV) and an electric vehicle (BEV). That is, the technology disclosed in the present invention also has the following aspects: a vehicle having one or both of the solid battery and liquid battery disclosed in the present invention.

[0203] 4. Effect

[0204] As described above, the positive electrode active material according to the first embodiment has low resistance when used in a solid battery, and the positive electrode active material according to the second embodiment has excellent rate characteristics when used in a liquid battery.

[0205] Example

[0206] As described above, the embodiments of the manufacturing method of the positive electrode active material, the positive electrode active material and the battery are described, but the technology of the present disclosure can be variously changed outside the above-mentioned embodiments without departing from the scope of its purpose. The following examples are shown to further explain the technology of the present disclosure in detail, and the technology of the present disclosure is not limited to the following examples.

[0207] 1. Preparation of positive electrode active material

[0208] 1.1 Positive active material A

[0209] 1.1.1 Preparation of precursor particles a1

[0210] (1) MnSO4·5H2O, NiSO4·6H2O, and CoSO4·7H2O were weighed to obtain a target composition ratio and dissolved in distilled water to a concentration of 1.2 mol / L to obtain a first solution. In addition, Na2CO3 was dissolved in distilled water in another container to a concentration of 1.2 mol / L to obtain a second solution.

[0211] (2) 1000 mL of pure water was placed in a reaction container (with baffles), and 500 mL of the first solution and 500 mL of the second solution were added dropwise thereto at a rate of about 4 mL / min.

[0212] (3) After the dropwise addition was completed, the mixture was stirred at room temperature at a stirring speed of 150 rpm for 1 hour to obtain a product.

[0213] (4) The product is washed with pure water, separated into solid and liquid using a centrifuge, and the precipitate is recovered.

[0214] (5) The obtained precipitate was dried at 120°C overnight, crushed in a mortar, and then separated into coarse particles a1-1 and fine particles a1-2 by air flow classification. The coarse particles a1-1 and fine particles a1-2 are both composite salts containing Mn, Ni and Co. The coarse particles a1-1 have an average particle size D50 of 4.0 μm and are spherical particles. In addition, the fine particles a1-2 have an average particle size D50 of 1.8 μm and are spherical particles.

[0215] (6) As the precursor particles a1, coarse particles a1-1 are used.

[0216] 1.1.2 Preparation of composite particles a2

[0217] (1) Na 2 CO 3 and distilled water were weighed to give 1150 g / L, and then stirred with a stirrer until the mixture was completely dissolved to prepare a Na 2 CO 3 aqueous solution.

[0218] (2) The Na2CO3 aqueous solution and the precursor particles a1 are weighed and mixed so that the composition after calcination described below becomes Na 0.7 Mn 0.5 Ni 0.2 Co 0.3 O2, thereby obtaining a slurry.

[0219] (3) The slurry was dried by air flow using spray drying to obtain composite particles a2. Specifically, a spray drying device DL410 was used at a slurry feeding rate of 30 mL / min, an inlet temperature of 200°C, and a circulating air volume of 0.8 m 3 The slurry was dried by air flow at 0.100 rpm and a spray pressure of 0.3 MPa to coat the surface of the precursor particle a1 with Na2CO3, thereby obtaining composite particles a2. In the composite particles a2, 77% by area of ​​the surface of the precursor particle a1 was coated with Na2CO3.

[0220] 1.1.3 Calcination of composite particles a2

[0221] The composite particles a2 were placed in an alumina crucible and fired in an air atmosphere to obtain Na-containing oxide particles a3 having a P2 type structure. The firing conditions were as described below (1) to (7).

[0222] (1) An alumina crucible containing the composite particles a2 is placed in a heating furnace in an air atmosphere.

[0223] (2) The temperature in the heating furnace was raised from room temperature (25°C) to 600°C over 115 minutes.

[0224] (3) The temperature in the heating furnace is maintained at 600° C. for 360 minutes for preliminary calcination.

[0225] (4) After the pre-sintering, the temperature in the heating furnace was raised from 600°C to 900°C over 100 minutes.

[0226] (5) Maintain the temperature in the heating furnace at 900°C for 60 minutes to perform main sintering.

[0227] (6) After the main firing, the temperature in the heating furnace was lowered from 900°C to 250°C over 120 minutes.

[0228] (7) The alumina crucible was taken out of the heating furnace at 250°C and allowed to cool in a dry atmosphere outside the furnace to 25°C over 10 minutes.

[0229] The calcined product after cooling was pulverized in a mortar in a dry atmosphere to obtain Na-containing oxide particles a3 having a P2-type structure (P2-type particles a3). The P2-type particles a3 had an average particle diameter D50 of 3.2 μm and were spherical particles.

[0230] 1.1.4 Ion exchange

[0231] (1) LiNO 3 and LiCl were weighed to a molar ratio of 50:50, and mixed with the above-mentioned P2 type particles a3 at a molar ratio of 10 times the minimum amount of Li required for ion exchange to obtain a mixture.

[0232] (2) Using an alumina crucible, ion exchange was performed in an air atmosphere at 280° C. for 1 hour to obtain a product containing an oxide containing Li.

[0233] (3) The salt remaining in the product was washed with pure water, and solid-liquid separation was performed by vacuum filtration to obtain a precipitate.

[0234] (4) The obtained precipitate was dried at 120° C. overnight to obtain a positive electrode active material A.

[0235] 1.2 Positive electrode active material B

[0236] 1.2.1 Preparation of precursor particles b1

[0237] As the precursor particles b1, the above-mentioned fine particles a1-2 are used.

[0238] 1.2.2 Preparation and sintering of composite particles b2

[0239] Composite particles b2 were prepared in the same manner as above except that precursor particles b1 were used instead of precursor particles a1. Composite particles b2 were sintered to obtain oxide particles b3 containing Na having a P2 type structure (P2 type particles b3). P2 type particles b3 had an average particle size D50 of 1.8 μm and were spherical particles.

[0240] 1.2.3 Ion exchange

[0241] Positive electrode active material B was obtained by performing ion exchange in the same manner as above except that P2 type particles b3 were used instead of P2 type particles a3.

[0242] 1.3 Positive electrode active material C

[0243] 1.3.1 Preparation of precursor particles c1

[0244] (1) MnSO4·5H2O, NiSO4·6H2O, and CoSO4·7H2O were weighed to obtain a target composition ratio and dissolved in distilled water to a concentration of 2 mol / L to obtain a first solution. In addition, Na2CO3 was dissolved in distilled water in another container to a concentration of 2 mol / L to obtain a second solution.

[0245] (2) 1000 mL of pure water was placed in a reaction container (with baffles), and 900 mL of the first solution and 900 mL of the second solution were added dropwise thereto at a rate of about 4 mL / min.

[0246] (3) After the dropwise addition was completed, the mixture was stirred at room temperature at a stirring speed of 150 rpm for 1 hour to obtain a product.

[0247] (4) The product is washed with pure water, separated into solid and liquid using a centrifuge, and the precipitate is recovered.

[0248] (5) The obtained precipitate was dried at 120°C overnight, crushed in a mortar, and then separated into coarse particles c1-1 and fine particles c1-2 by air flow classification. The coarse particles c1-1 and fine particles c1-2 were both composite salts containing Mn, Ni, and Co. The coarse particles c1-1 had an average particle size D50 of 4.8 μm and were spherical particles.

[0249] (6) As the precursor particles c1, coarse particles c1-1 are used.

[0250] 1.3.2 Preparation and sintering of composite particles c2

[0251] Composite particles c2 were prepared in the same manner as above except that precursor particles c1 were used instead of precursor particles a1, and the composite particles c2 were sintered to obtain Na-containing oxide particles c3 having a P2-type structure (P2-type particles c3). The P2-type particles c3 had an average particle size D50 of 4.3 μm and were spherical particles.

[0252] 1.3.3 Ion exchange

[0253] Ion exchange was carried out in the same manner as above, to obtain a positive electrode active material C, except that P2 type particles c3 were used instead of P2 type particles a3.

[0254] 1.4 Positive electrode active material D

[0255] 1.4.1 Preparation of precursor particles d1

[0256] As the precursor particles d1, the above-mentioned fine particles a1-2 are used.

[0257] 1.4.2 Preparation of composite particles d2

[0258] Weigh the precursor particles d1 and Na2CO3 so that Na 0.7 Mn 0.5 Ni 0.2 Co 0.3 The weighed precursor particles d1 and Na2CO3 were mixed in a mortar to obtain composite particles d2. In the composite particles d2, 22% by area of ​​the surface of the precursor particles d1 was covered with Na2CO3.

[0259] 1.4.3 Calcination of composite particles d2

[0260] The composite particles d2 were sintered in the same manner as above except that the composite particles d2 were used instead of the composite particles a2 to obtain Na-containing oxide particles d3 having a P2-type structure (P2-type particles d3). The P2-type particles d3 had an average particle size D50 of 1.3 μm and were plate-like particles.

[0261] 1.4.4 Ion exchange

[0262] Ion exchange was carried out in the same manner as above, to obtain a positive electrode active material D, except that P2 type particles d3 were used instead of P2 type particles a3.

[0263] 2. Evaluation of positive electrode active materials

[0264] 2.1 Elemental analysis and crystal structure identification

[0265] Elemental analysis was performed on each of the positive electrode active materials A to D, and the target composition was obtained. In addition, X-ray diffraction measurement was performed, and the results showed that the positive electrode active materials A to D all had an O2 type structure.

[0266] 2.2 Determination of average particle size and specific surface area

[0267] For each positive electrode active material A to D, the average particle size D50 and the BET specific surface area were measured. The average particle size D50 is the particle size (median diameter) at the cumulative value of 50% in the volume-based particle size distribution using the laser diffraction and scattering method. In addition, the BET specific surface area is measured using a gas adsorption method. Specifically, a specific surface area / pore distribution measuring device (Micromeritics, Tristar) was used to perform a measurement using a constant volume method with nitrogen as the adsorbed gas. That is, a glass tube containing a sample is immersed in liquid nitrogen, the tube is evacuated, and then the relative pressure (= adsorption equilibrium pressure / saturated vapor pressure) is changed to measure the amount of adsorbed nitrogen. The BET specific surface area was calculated from the measured amount of adsorbed nitrogen and relative pressure.

[0268] 2.3 Observation of shape

[0269] The appearance and cross-sectional shape of the positive electrode active materials A to D were observed using SEM. Figure 4 : The SEM image of the cross-sectional shape is shown in FIG. The positive electrode active material A is a spherical particle having a hollow single-layer structure. The positive electrode active material B is a spherical particle having a hollow single-layer structure. The positive electrode active material C is a spherical particle having a hollow multilayer structure. The positive electrode active material D is a plate-like particle.

[0270] 3. Preparation of evaluation battery cells

[0271] 3.1 Fabrication of solid-state batteries

[0272] Solid-state batteries were fabricated using each positive electrode active material. The fabrication steps of the solid-state batteries are as follows.

[0273] (1) The positive electrode active material, sulfide solid electrolyte A (argyrodite-type sulfide solid electrolyte), PVDF and VGCF were weighed and mixed so that the positive electrode active material: sulfide solid electrolyte A: PVDF: VGCF = 82.1: 14.9: 0.6: 2.4 (mass ratio), thereby obtaining a positive electrode composite material.

[0274] (2) Weigh and mix the negative electrode active material (Li 15 Si4 and Si single substance), sulfide solid electrolyte B (Li2S-P2S5-LiI-LiBr), PVDF and VGCF to become Li 15S4: Si element: sulfide solid electrolyte B: PVDF: VGCF = 30.5: 50.7: 15.5: 0.9:

[0275] 2.4 (mass ratio), thereby obtaining a negative electrode composite material.

[0276] (3) Sulfide solid electrolyte B and acrylate butadiene rubber (ABR) were weighed and mixed so as to have sulfide solid electrolyte B:ABR=99.4:0.6 (mass ratio), thereby obtaining an electrolyte composite material.

[0277] (4) The above electrolyte composite was placed in a Macor cylindrical container and pressed at 9.8 kN for 1 minute to form an electrolyte layer. Then, the above positive electrode composite was placed on one side of the electrolyte layer and pressed at 19.6 kN for 1 minute to form a positive electrode active material layer. Furthermore, the above negative electrode composite was placed on the other side of the electrolyte layer and pressed at 58 kN for 3 minutes to form a negative electrode active material layer. Finally, current collectors were placed at both ends of the stacking direction of each layer to obtain a solid battery.

[0278] 3.2 Fabrication of Liquid-System Batteries

[0279] Liquid-system batteries were fabricated using each positive electrode active material. The steps for fabricating the liquid-system batteries are as follows.

[0280] (1) The positive electrode active material, acetylene black (AB) as a conductive aid, and polyvinylidene fluoride (PVdF) as a binder were weighed so that the mass ratio was positive electrode active material: AB: PVdF = 85:10:5, and dispersed and mixed in N-methyl-2-pyrrolidone to obtain a positive electrode composite slurry. The positive electrode composite slurry was coated on an aluminum foil and vacuum dried at 120°C overnight to obtain a positive electrode as a laminate of a positive electrode active material layer and a positive electrode collector.

[0281] (2) LiPF6 was dissolved at a concentration of 1 M in a mixed solvent of trifluoropropylene carbonate (TFPC) and trifluoromethyl ethyl carbonate (TFEMC) at a ratio of TFPC:TFEMC=30 volume %:70 volume %, to obtain an electrolyte solution.

[0282] (3) As a negative electrode, a metal lithium foil was prepared.

[0283] (4) A coin battery cell (CR2032) was produced as a liquid-based battery using a positive electrode, an electrolyte solution, and a negative electrode.

[0284] 4. Evaluation of battery cells

[0285] 4.1 Determination of discharge capacity of solid state batteries

[0286] The solid battery was charged and discharged in a thermostatic chamber maintained at 25° C. at a voltage range of 1.8 to 4.6 V and a rate of 0.1 C (1 C = 220 mA / g), and the discharge capacity was measured.

[0287] 4.2 Determination of DCIR resistance of solid battery

[0288] The solid battery was charged and discharged twice in a constant temperature chamber maintained at 25°C at a voltage range of 1.8-4.6V and a rate of 0.1C (1C = 220mA / g). Then, a current equivalent to 3C was applied for 10s at SOC 50% to measure the DCIR resistance.

[0289] 4.3 Liquid battery

[0290] Each coin cell was charged and discharged in a thermostatic chamber maintained at 25°C at a voltage range of 2.0-4.8V and a rate of 0.1C or 3C (1C = 220 mA / g), and the capacity at 0.1C and 3C were measured.

[0291] 5. Evaluation results

[0292] The evaluation results of the positive electrode active material are shown in the following Tables 1 and 2. In addition, the evaluation results of the solid battery are shown in the following Table 1. In addition, the evaluation results of the liquid battery are shown in the following Table 2.

[0293]

Table 1

[0294] (Table 1: Solid-state batteries)

[0295]

[0296]

Table 2

[0297] (Table 2: Liquid battery)

[0298]

[0299] From the results shown in Table 1, it can be seen that positive electrode active materials A and B have low resistance when applied to solid batteries. In addition, from the results shown in Table 2, it can be seen that positive electrode active material C has excellent rate characteristics when applied to liquid batteries.

[0300] 6. Supplement

[0301] Furthermore, in the above-mentioned embodiment, the case where the precursor particles are obtained by the coprecipitation method is illustrated, but the precursor particles can also be obtained by methods other than this. In addition, in the above-mentioned embodiment, the case where the surface of the precursor particles is coated with a Na source by spray drying to obtain composite particles is illustrated, but the composite particles can also be obtained by methods other than this. In addition, in the above-mentioned embodiment, as the oxide containing Na with a P2 type structure and the oxide containing Li with an O2 type structure, an oxide with a prescribed chemical composition is illustrated, and the chemical composition of the oxide containing Na and the oxide containing Li is not limited thereto. In addition, the oxide containing Na and the oxide containing Li can be doped with an element M other than Mn, Ni and Co. For the element M, as described in the embodiment.

[0302] 7. Summary

[0303] As described above, in the case of a positive electrode active material comprising an oxide containing Li, when the oxide containing Li satisfies the following characteristics (1) to (3), the resistance is reduced when the positive electrode active material is used in a solid battery.

[0304] (1) The above-mentioned Li-containing oxide particles have an O2 type structure.

[0305] (2) The Li-containing oxide particles are spherical particles having a hollow single-layer structure.

[0306] (3) The Li-containing oxide particles have an average particle size of 1.0 μm or more and less than 3.5 μm.

[0307] On the other hand, a positive electrode active material comprising an oxide containing Li has excellent rate characteristics when used in a liquid battery when the oxide containing Li satisfies the following characteristics (4) to (6).

[0308] (4) The above-mentioned Li-containing oxide particles have an O2 type structure.

[0309] (5) The Li-containing oxide particles are spherical particles having a hollow multilayer structure.

[0310] (6) The Li-containing oxide particles have an average particle size of 3.5 μm or more.

[0311] In addition, the Li-containing oxide particles satisfying the above characteristics (1) to (3) and the Li-containing oxide particles satisfying the above characteristics (4) to (6) can be produced by distinguishing, for example, the size of the P2 type particles before ion exchange.

Claims

1. A method for producing a positive electrode active material for a solid battery, comprising: Obtaining Na-containing oxide particles having a P2-type structure; and At least a portion of Na in the Na-containing oxide particles is ion-exchanged with Li to obtain Li-containing oxide particles having an O2-type structure, The Na-containing oxide particles are spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm. The Li-containing oxide particles are spherical particles having a hollow single-layer structure.

2. The manufacturing method according to claim 1, wherein: The Na-containing oxide particles contain at least one element of Mn, Ni, and Co, Na, and O as constituent elements.

3. A positive electrode active material, which is a positive electrode active material for a solid battery, comprising oxide particles containing Li, wherein the oxide particles containing Li have an O2 type structure, the oxide particles containing Li are spherical particles with a hollow single-layer structure, and the oxide particles containing Li have an average particle size of greater than 1.0 μm and less than 3.5 μm.

4. The positive electrode active material according to claim 3, wherein The Li-containing oxide particles have a particle size of less than 4.5 μm. 2 / g specific surface area.

5. The positive electrode active material according to claim 3 or 4, wherein The Li-containing oxide particles contain at least one element of Mn, Ni, and Co, Li, and O as constituent elements. 6 . A solid battery comprising a positive electrode active material layer, an electrolyte layer and a negative electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material according to claim 3 , and the positive electrode active material layer comprises a solid electrolyte.

7. A method for producing a positive electrode active material for a liquid battery, comprising: Obtaining Na-containing oxide particles having a P2-type structure; and At least a portion of Na in the Na-containing oxide particles is ion-exchanged with Li to obtain Li-containing oxide particles having an O2-type structure, The oxide particles containing Na are spherical particles having an average particle size of 3.5 μm or more, and the oxide particles containing Li are spherical particles having a hollow multilayer structure.

8. The manufacturing method according to claim 7, wherein: The Na-containing oxide particles contain at least one element of Mn, Ni, and Co, Na, and O as constituent elements.

9. A positive electrode active material, which is a positive electrode active material for a liquid battery, comprising oxide particles containing Li, wherein the oxide particles containing Li have an O2 type structure, the oxide particles containing Li are spherical particles with a hollow multilayer structure, and the oxide particles containing Li have an average particle size of more than 3.5 μm.

10. The positive electrode active material according to claim 9, wherein The Li-containing oxide particles have a 4.5 m 2 / g or more specific surface area.

11. The positive electrode active material according to claim 9 or 10, wherein The Li-containing oxide particles contain at least one element of Mn, Ni, and Co, Li, and O as constituent elements.

12. A liquid battery comprising a positive electrode active material layer, an electrolyte layer and a negative electrode active material layer, wherein: The positive electrode active material layer includes the positive electrode active material according to any one of claims 9 to 11, and the positive electrode active material layer includes a liquid electrolyte.

Citation Information

Patent Citations

  • Non-aqueous electrolyte secondary battery and method of manufacturing the same

    JP2011170994A